ИЗУЧЕНИЕ СПЕКТРАЛЬНЫХ ХАРАКТЕРИСТИК ЭЭГ У ДОЛГОЖИТЕЛЕЙ ИЗ РАЗЛИЧНЫХ ЭКОЛОГО-ГЕОГРАФИЧЕСКИХ ЗОН АПШЕРОНСКОГО ПОЛУОСТРОВА (Experimental biology, 2015)
In the given work, using a method computer electroencephalography, the functional condition of a brain of the healthy longlivers lived in various ekologo-geographical conditions is analysed. Comparative research has shown that EEG activity at the long-livers living in adverse ecologicalconditions, is characterized by low level of functional activity of a brain
Keywords: ecologicalcondition; computer electroencephalography